2015
DOI: 10.14503/thij-14-4572
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Oral Anticoagulation in Stroke Prevention among Sinus-Rhythm Patients Who Lack Left Atrial Mechanical Contraction after Cryoablation

Abstract: The customary recommendation is that oral anticoagulation be withdrawn a few months after cryoablation for atrial fibrillation, independently of left atrial mechanical contraction in patients in sinus rhythm. Recently, a 5-fold increase in stroke has been described in sinus-rhythm patients who lack atrial mechanical contraction. One aim of this study was to evaluate the efficacy of oral anticoagulation in preventing postoperative stroke in such patients. This prospective study divided 154 sinus-rhythm patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
(15 reference statements)
0
5
0
Order By: Relevance
“…The decision to discontinue anticoagulant should not be weighed solely on rhythm conversion, but should also take atrial contractility, clinical predictors, and the bleeding risk into consideration. 7,14,20 There were several limitations to our study. As it was a retrospective study, it had an inherent selection bias.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The decision to discontinue anticoagulant should not be weighed solely on rhythm conversion, but should also take atrial contractility, clinical predictors, and the bleeding risk into consideration. 7,14,20 There were several limitations to our study. As it was a retrospective study, it had an inherent selection bias.…”
Section: Discussionmentioning
confidence: 98%
“…Limited studies have reported no increased risk of thromboembolic stroke with anticoagulant discontinuation 6 months after a Cox maze in such patients. 14,20 However, there was not enough power to recommend anticoagulant discontinuation due to the nonrandomized, retrospective, observational nature of the studies. The decision to discontinue anticoagulant should not be weighed solely on rhythm conversion, but should also take atrial contractility, clinical predictors, and the bleeding risk into consideration.…”
Section: Discussionmentioning
confidence: 99%
“…Some have reported the return of haemodynamically meaningful function, but others have suggested that the maze procedure is unlikely to achieve functional recovery, despite restoring SR. 69 In patients without atrial contraction, anticoagulant drugs significantly reduce stroke rate, but the incidence of major bleeding is increased. 72,73 Furthermore, patients with chronic AF have evidence of persistent left atrial dysfunction, even after restoration of SR by radiofrequency ablation. This suggests that global and regional atrial dysfunction may be attributable to a combination of injury from the ablation process and pre-existing disease.…”
Section: Discussionmentioning
confidence: 99%
“…1 We have read the input with great interest as well as Dr. Martínez-Comendador's publication on left atrial mechanical contraction (LAMC) in the management of anticoagulation therapy post ablation. 2 In our study, anticoagulation therapy was discontinued if (a) sinus rhythm was documented by electrocardiogram, (b) atrial fibrillation was absent on 5-day Holter monitoring, (c) CHADS 2 score less than or equal to 2, and (d) no other indications for anticoagulation therapy were present. The rationale for not including LAMC in our study criteria was simply that LAMC was not established in the context of anticoagulation treatment in the early 2000s, when our first patients were operated.…”
Section: Left Atrial Mechanical Contraction In Discontinuation Of Anticoagulants After Surgical Ablation Of Atrial Fibrillation: a Responmentioning
confidence: 99%